The Effect of Total Body Resistance Exercise Variations on the Speed of Youth Pencak Silat Scythe Kicks - Keliat, Pedomanta; Situmorang, Satria; Simanullang, Samsul Bahari; Sagala, Satrio Gunawan; Zega, Setiawan Putra; Gulo, Sastra Jaya (Pusdikra-Publishing.com, 2024)
The magnitude of the sickle strike directly influences the number of match points that can be achieved in the martial art of Pencak Silat. The aim of this study is to undertake a comprehensive analysis of the impact of different types of Total Body Resistance Exercise training on the speed of Pencak silat sickle kicks performed by teenagers. This research methodology utilises a hypothetical inquiry that consists of two distinct groups: an experimental group and a control group. The subjects of this study were combatants who had engaged in the practice of Pencak silat at State Vocational High School (SMK) Negeri 1 Stabat. There were a total of 52 participants who met the requirements for this inquiry. The sample was gathered using purposive sampling, which followed the specified criteria. To participate, one must have attended Pencak silat training sessions at SMK N 1 Stabat, have a high level of skill in the fundamental methods of the sickle kick, be between the ages of 17 and 19, and be willing to serve as a study sample. The confirmation of eligibility for a group of 33 individuals, consisting of 17 girls and 16 males, resulted from the assessment of these specific criteria. This research apparatus is utilised to assess the speed of Pencak silat kicks and estimate the impact of sickle blows. Consequently, Total Body Resistance Exercise training affects the speed of sickle kicks. However, there is no noticeable statistically significant variation in sickle kick speed among adolescent Pencak Silat practitioners.